O compartilhamento de conhecimentos como estímulo para inovação : análise de uma rede instersetorial de serviços compartilhados - Fernandes, Carla Rosana (2017)
This work aims to expand the understanding about a phenomenon, not very current: innovation in interindustry networks associated with knowledge sharing. It brings concepts of Innovation, Knowledge and Interorganizational Relations. Through a unique case study, based on a qualitative and exploratory method, it discuss the relationships between knowledge sharing and innovation development in a network of interorganizational collaboration of shared services. The research identified, in the network context, that interindustriality and diversity in the size of organizations are elements that (1) favor the sharing of knowledge; (2) allow the creation of a favorable environment for closer relations between organizations and (3) collaborate in intraorganizational innovation processes. Participation, in this network format, allows its members to share not only successful experiences, reducing project time and cost. The study also pointed out opportunities for improvements to the generation of a virtuous cycle by the leaders of the network. At the intra-organizational level, leadership plays a role that supports the dissemination of knowledge in order to reach all levels of their respective organizations. At an interorganizational level, as their main executives represents the organizations within the network, their role is to emerge, apart from operational aspects, the development of broader discussions that raise strategic topics of mutual interest. The interaction environment in interindustry networks has proved to be relevant because it identifies a type of interorganizational relationship that allows the organizations that integrate it to be a kind of accelerator for its performance.